Síntese de inibidores potenciais de hexosaminidases derivados de N-acetilglicosamina e D-glicose - Lucas Lopardi Franco (Orbital: The Electronic Journal of Chemistry, 2012)
We report herein the synthesis and characterization of N-acetylglucosamine and D-glucose derivates modified at C-1 for evaluation of antifungal activity as potential hexosaminidases inhibitors. There are various related antifungal commercial drugs, but all of them have collateral damages like: irreversible kidney disease, hormonal disorders and antibiotic resistance. In this current scenario the study of new antifungal drugs that can act by a new mechanism is important. Several natural and synthetic hexosaminidases inhibitory are reported in the literature. These enzymes are critical for the biosynthesis and remodeling of chitin, important for fungi structure. Hexosaminidases inhibitors are generally monosaccharides derivates or analogs of N-acetylglucosamine.